Changes in Erythrocytes Osmotic Fragility and Sphericity Index in Rat’s of Different Ages Under Cold Exposures - Ostras, Daniil A.; Lutsenko, Dmytro G.; Lomako, Victoria V.; Kovalenko, Igor F.; Shylo, Oleksandr V. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 172.